Level of Integrity, Availability teachers, implementation of school-based assessment, Teaching Profession - Mohamad Nizam Bin Nazarudin; Norsyamsiah Binti Waridi; Ismail Bin Saad, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The purpose of this study is to study the impact of agility training programs on theimprovement of motor skills-based fitness components among control and treatment groups. Atotal of 32 novice rugby novels from the Show Rugby Club were randomly divided into controlgroups (N = 16) and treatment group (N = 16). The treatment group had undergone reactiveagility training program for 8 weeks while the control group undergoes traditional training.Statistical data analysis uses paired t - test and ANOVA repetitive measurements. The findingsshow that there is a difference in the effect of reactive agility training and traditional agilitytraining on motor-based fitness components. There is a significant difference in the mean scoreof speed test, agility, balance and reaction time p = <.05 between treatment groups and controlgroups. There was no significant difference p => .05, for the coordination and control testsbetween control and treatment groups. The treatment group has shown a better improvementcompared to the control group. This proves that reactive dexterity training using i - Agile systemsoftware has improved the physical fitness component based on motorists among novice rugbyplayers better than traditional training methods. Teen novels rugby trainers need to change to theuse of reactive agility training in their training sessions. There is a need now to make moreinnovations and further studies on reactive agility training in the future.